Perwaja Steel: Case and Instructor's Manual - Chui Yan, Yap (2010)
On 20 August 2008, Perwaja reached a new milestone in its history by making its debut on the main board of Bursa Malaysia Securities Berhad. At an initial public offering (IPO) price of RM2.90, the shares were oversubscribed by 189%. Since then, however, the company’s stock had traded at below its IPO price, reaching a low of RM0.60 in March 2009. In mid-2009, the company reported net losses exceeding RM100 million for the first half of 2009 compared to profits of more than RM200 million for the same period in 2008. This was attributed partly to the decrease in steel demand and prices worldwide amidst the global recession. Henry Pheng, Perwaja’s CEO, told Reuters in an interview in March 2009 that the goal for the year was to ride out the recession by planning purchases carefully and taking other cost-saving measures rather than to make profits. Industry observers, however, wondered how much more market uncertainties the company could withstand and what strategic moves it would make to strengthen its market position and succeed in the competitive and volatile steel industry.